Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Simplify:(m+2)(m+m)-pm; use m = -8, and p = -2-112-4None of these answers are correct.20-34

Sagot :

ANSWER

None of these options are correct.

EXPLANATION

We want to simplify the expression given:

(m + 2)(m + m) - pm

We have that m = -8 and p = -2.

Therefore, it becomes:

(-8 + 2)(-8 - 8) - (-2)(-8)

= (-6)(-16) -(16)

= 96 - 16

= 80

Therefore, none of the given options are correct.